Management of a case of Mucor colonization in breast tissue expander seroma pocket. (June 2017) - Atwood, Danielle N.; Yuen, James C.; Yuen, Brian; Kumbla, Pallavi A.
Abstract: Mucormycosis is a rare and potentially life-threatening opportunistic infection with approximately 500 cases per year in the United States (Spellberg et al., 2005). There are six major presentations, which include rhino-orbital-cerebral, pulmonary, cutaneous, gastrointestinal, disseminated, and uncommon (e.g. osteomyelitis, endocarditis) Petrikkos et al. (2012). 2 While not a prominent pathogen in immunocompetent patients, immunocompromised patients such as those with prolonged neutropenia, organ and/or bone marrow suppression, and diabetes mellitus are prone to dissemination resulting in rapid death without prompt intervention (Spellberg et al. 2005). With a mortality rate reaching 90% (Spellberg et al. 2005), it is imperative that therapy be initiated rapidly once a diagnosis is made. Successful treatment consists of management of underlying risk factors, surgical debridement, and antifungal therapies (Spellberg et al. 2005). The dilemma whether to pursue extensive debridement presents when the wound is cultured positive but the patient is not systemically ill. We present the first reported case of successful salvage of breast reconstruction with retention of tissue extender and acellular dermal matrix (ADM) despite colonization of a recalcitrant seroma pocket by Mucor .